AFTERSHOCK CHARACTERISTICS OF THE 2018 PALU EARTHQUAKE: IMPLICATIONS FOR SUPERSHEAR RUPTURE SEGMENT - Muzli Muzli; Karen H Lythgoe; Rayhan Irfan Hielmy; Rahmat Triyono; Shengji Wei (Universitas Mataram, 2026)
A temporary nodal array was deployed shortly after the Mw 7.5 Palu earthquake in September 2018 to record the aftershocks. Here, we present high-resolution aftershock locations and moment tensors, obtained from the temporary array combined with permanent broadband stations. The results are used to define the fault geometry and seismogenic depth. We find that there are very few aftershocks along a long, straight section of the Palu-Koro fault, which ruptured at supershear speed. Aftershocks tend to cluster north and south of this straight section. Secondary strike-slip faults to the south and east of the main fault were triggered. Additionally, we record an earthquake swarm occurring in the Adang volcanic zone, which began approximately 1 month after the mainshock. Given the smaller number and lower magnitude of aftershocks, we suggest that supershear ruptures pose a lower seismic hazard than corresponding subshear earthquakes. However, the strong shaking from a supershear rupture may pose other hazards, such as disastrous liquefaction. Lastly, we suggest that the ability to deploy short-period nodal arrays rapidly makes them a powerful tool for aftershock studies.